2019
DOI: 10.3390/biom9050174
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin and Quercetin: Promising Flavonoids with Chemopreventive Potential

Abstract: Despite advancements in healthcare facilities for diagnosis and treatment, cancer remains the leading cause of death worldwide. As prevention is always better than cure, efficient strategies are needed in order to deal with the menace of cancer. The use of phytochemicals as adjuvant chemotherapeutic agents in heterogeneous human carcinomas like breast, colon, lung, ovary, and prostate cancers has shown an upward trend during the last decade or so. Flavonoids are well-known products of plant derivatives that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(126 citation statements)
references
References 184 publications
(191 reference statements)
0
120
0
6
Order By: Relevance
“…Although numerous reports have described the proapoptotic effects of flavonoids and thus their possible use in cancer prevention [ 142 , 143 ], several flavonoids have also been shown to have potent antiapoptotic activity and protect cells against damage caused by various stimuli, both in vitro and in vivo in animal disease models. The involved mechanisms include the inhibition of the intrinsic apoptotic pathway by the preservation of mitochondrial function (i.e., maintaining mΔΨ), regulation of redox potential and MOMP by downregulation of BAX and BAK or upregulation of BCL-2 and BCL-xL [ 144 ].…”
Section: Flavonoids In Mitochondrial Pathwaysmentioning
confidence: 99%
“…Although numerous reports have described the proapoptotic effects of flavonoids and thus their possible use in cancer prevention [ 142 , 143 ], several flavonoids have also been shown to have potent antiapoptotic activity and protect cells against damage caused by various stimuli, both in vitro and in vivo in animal disease models. The involved mechanisms include the inhibition of the intrinsic apoptotic pathway by the preservation of mitochondrial function (i.e., maintaining mΔΨ), regulation of redox potential and MOMP by downregulation of BAX and BAK or upregulation of BCL-2 and BCL-xL [ 144 ].…”
Section: Flavonoids In Mitochondrial Pathwaysmentioning
confidence: 99%
“…Along with protecting cells from oxidative stress, flavonoids can promote apoptosis and genotoxicity of tumor cells through pro-oxidant activities [ 14 , 15 ]. In addition to the pro-oxidative action and the initiation of apoptosis, other anti-tumorigenic mechanisms of QU action include inhibition of glycolysis and enzyme synthesis, interaction with estrogen type II binding sites, and modulation of numerous molecular targets [ 16 , 17 , 18 ]. The antitumor activity of QU has been investigated in different types of cancers including breast, colon, gastric, leukemia, melanoma, head and neck, and bladder cells [ 13 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin is one of the most prevalent plant flavonoids contained in many fruits and vegetables. Within the flavonoid family, quercetin is the most potent scavenger of ROS [ 33 , 34 ]. Previous studies reported that quercetin could ameliorate pulmonary fibrosis, renal fibrosis, liver fibrosis [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%